From stress to sight: The role of mechanical forces in the retinal diseases - Di Wu; Ye Liu; Xiaogang Luo; Chengshou Zhang; Yifei Zheng; Jianfeng Meng; Mei Yang; Hemlata Bisnauthsing; Ping Rao; Baohua Ji; Wai Kit Chu (Advances in Ophthalmology Practice and Research)
Background: The retina, a light-sensitive neural tissue critical for vision, exists in a dynamic mechanical environment where it is continuously exposed to mechanical forces. These forces, including traction forces, intraocular pressure-related stress, and hemodynamic forces, are closely linked to the progression of retinal diseases. A comprehensive understanding of retinal mechanosensation and mechanotransduction is essential for understanding the pathological mechanisms under aberrant mechanical conditions. Main Text: This review synthesizes current knowledge on advanced biomechanical assessment techniques, and aging-associated biomechanical alterations in retinal tissues, emphasizing how mechanical forces drive structural and functional pathology. Conclusions: By elucidating the mechanosensitive mechanisms remodeling retinal cell behavior and fate, this review highlights the critical role of biomechanics in retinal disease pathogenesis. The integration of mechanistic insights with biomechanical assessment techniques offers transformative potential for diagnosing mechanical dysfunction and developing mechanotargeted therapies.